1958
DOI: 10.1063/1.1705871
|View full text |Cite
|
Sign up to set email alerts
|

Some Further Results on the Bénard Problem

Abstract: The exact solution of the sixth-order differential equation which governs the stability of a viscous fluid contained between two rigid walls and heated from below is briefly reviewed and extended to include detailed results on the curve of neutral stability and the cell pattern at the onset of instability. Two approximate methods of solution are then discussed which employ a Fourier or Fourier-type expansion and which require the solution of only a fourth- or a second-order differential equation. A comparison … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
45
0
1

Year Published

1963
1963
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(58 citation statements)
references
References 9 publications
12
45
0
1
Order By: Relevance
“…3, the solid straight line is drawn through the data points using the least-squares fitting and the intersection with the horizontal axis gives the critical Rayleigh number. The calculated critical Rayleigh number is 1708.48 and agrees well with the theoretical value of 1707.76 obtained by linear stability theory [25] within 0.042 %.…”
Section: Numerical Resultssupporting
confidence: 76%
“…3, the solid straight line is drawn through the data points using the least-squares fitting and the intersection with the horizontal axis gives the critical Rayleigh number. The calculated critical Rayleigh number is 1708.48 and agrees well with the theoretical value of 1707.76 obtained by linear stability theory [25] within 0.042 %.…”
Section: Numerical Resultssupporting
confidence: 76%
“…Following the procedure described in [37,38,39], we adopted the even solution which has minimum critical effective Rayleigh number. Our numerical analysis showed that the anisotropy of turbulent The effective Rayleigh number versus the aspect ratio L z /L ⊥ of the perturbations for two rigid boundaries is plotted in Fig.…”
Section: B Solution For Two Rigid Boundariesmentioning
confidence: 99%
“…There is experimental evidence for such a process. 15 But the presence of such distortions does not explain why in fully developed turbulence the longitudinal vortices seem to play a more important part than transverse vortices. It is as if they completely take over the role of the latter in keeping up the mixing process between the horizontal layers, which is characteristic for turbulence.…”
mentioning
confidence: 99%
“…Mathematical investigations have been carried out by Lord Rayleigh, H. Jeffreys, and A. R. Low; see for instance [14]. Some newer calculations have been given by W. H. Reid and D. L. Harris, see [15].…”
mentioning
confidence: 99%
See 1 more Smart Citation